MENGOPTIMALKAN ALIRAN INFORMASI UNTUK MENINGKATKAN KOMUNIKASI ORGANISASI DAN PROSES PENGAMBILAN KEPUTUSAN DI ORGANISASI MODERN - Anindita Sauqania; Andriano Purnama; Marsalia Diandra Putri; Mohamad Muspawi (STKIP Subang, 2026)
Information plays a crucial role in supporting organizational activities, particularly in communication and decision-making processes. Effective information flow enables organizations to coordinate tasks, share knowledge, and respond to various organizational challenges more efficiently. However, ineffective information flow can create communication barriers, delays in information delivery, and inaccurate decision-making. Therefore, optimizing information flow within an organization is crucial for improving organizational communication and decision-making processes. This study aims to analyze the role of information flow in improving organizational communication and supporting effective decision-making in modern organizations. This study uses a qualitative approach with a literature review method through a review of various academic sources such as scientific journals, books, and previous research related to organizational communication and information flow. The results show that effective information flow can support better coordination among organizational members, increase transparency, and provide accurate information in the decision-making process. In addition, the use of information technology, an open communication culture, and effective coordination between organizational units are important factors in optimizing information flow. Thus, optimizing information flow can improve the effectiveness of organizational communication and support better decision-making in modern organizations